Learning and inclusivity via Interactive Groups in early childhood education and care in the Hope school, Spain. (June 2017) - Aubert, Adriana; Molina, Silvia; Schubert, Tinka; Vidu, Ana
Abstract: Access to high-quality early childhood education and care (ECEC), particularly for disadvantaged children, is critical to ensuring that future learning is more effective and more likely to continue throughout life. A wealth of research has provided extensive information about the key factors that impact the quality of ECEC and improve cognitive and social outcomes. Despite the European priority to make high-quality ECEC available to all children, accomplishing this goal remains a challenge. The present article discusses a specific type of inclusive classroom organisation called Interactive Groups (IGs). IGs were studied in the preschool classrooms of an urban school located in a disadvantaged area of Spain that has high levels of unemployment, poverty and marginalisation. Empirical data from interviews with teachers, daily life stories from mothers and children, and classroom observations shed light on the perceptions of the potential of this particular classroom setting, where children are placed in small, mixed-ability groups coordinated by one volunteer from the community, to benefit children and promote their cognitive, social and emotional development. The findings suggest that this particular form of inclusive classroom organisation can reach children from a minority background while providing high-quality ECEC.